The regulation of religious communities in the late middle ages: a comparative approach to Ming China and pre-reformation England - Li, Teng; Salonia, Matteo (2020)
This article examines the regulation of religious life in the late Middle Ages (14th and 15th centuries), focusing comparatively on Catholic monastic communities in pre-Reformation England and Buddhist monasticism in early Ming China. This comparative approach to two of the most important monastic traditions across Eurasia allows us to problematize the paradigm of ideas and praxes surrounding monastic self-governance in Latin Christendom and to integrate the current scholarship on Ming regulation of religious communities by investigating the pivotal changes in imperial religious policies taking place in the early period of this dynasty. We find that monks and secular authorities at the two ends of Eurasia often shared the same concerns about the discipline of religious men and women, the administration of their properties, and the impact of these communities on society at large. Yet, the article identifies significant differences in the responses given to these concerns. Through the analysis of primary sources that have thus far been overlooked, we show how in early Ming China the imperial government imposed a strict control over the education, ordination and disciplining of Buddhist monks. This bureaucratic system was especially strengthened during the reign of Zhu Yuanzhang (r. 1368–1398), when the figure of the Monk-Official and other tools of secular regulation were introduced, and limits to property claims and economic activities of monasteries were imposed. Instead, during the same period, English monasteries benefited from the previous disentangling of the Church from secular political authorities across Europe. In fact, in late medieval England, the Benedictine tradition of self-governance and independence from the secular sphere was arguably even more marked than in the rest of the continent.